Traumatic Brain Injury Accelerates the Onset of Cognitive Dysfunction and Aggravates Alzheimer's-Like Pathology in the Hippocampus by Altering the Phenotype of Microglia in the APP/PS1 Mouse Model - Wu, Di; Kumal, Jay Prakash P.; Lu, Xiaodi; Li, Yixuan; Mao, Dongsheng; Tang, Xudong; Nie, Meitong; Liu, Xin; Sun, Liang; Liu, Bin; Zhang, Yafang (Frontiers in Neurology, 2021)
An increasing number of studies have suggested that traumatic brain injury (TBI) is associated with some neurodegenerative diseases, including Alzheimer's disease (AD). Various aspects of the mechanism of TBI-induced AD have been elucidated. However, there are also studies opposing the view that TBI is one of the causes of AD. In the present study, we demonstrated that TBI exacerbated the disruption of hippocampal-dependent learning and memory, worsened the reductions in neuronal cell density and synapse formation, and aggravated the deposition of Aβ plaques in the hippocampi of APP/PS1 mice. We also found that TBI rapidly activated microglia in the central nervous system (CNS) and that this effect lasted for at least for 3 weeks. Furthermore, TBI boosted Aβ-related microglia-mediated neuroinflammation in the hippocampi of APP/PS1 mice and the transformation of microglia toward the proinflammatory phenotype. Therefore, our experiments suggest that TBI accelerates the onset of cognitive dysfunction and Alzheimer-like pathology in the APP/PS1 mouse model, at least partly by altering microglial reactions and polarization.